Administration of exogenous 1, 25(OH)2D3 normalizes overactivation of the central renin-angiotensin system in 1α(OH)ase knockout mice. (19th February 2015) - Zhang, Wei; Chen, Lulu; Zhang, Luqing; Xiao, Ming; Ding, Jiong; Goltzman, David; Miao, Dengshun
Highlights: 1-alpha-hydroxylase knockout mice show hypertension. Vitamin D normalizes brain RAS alteration in active vitamin D defeciency mice. Vitamin D normalizes central oxidative stress in the mice. Vitamin D exerts anti-hypertensive effects in part via its antioxidative effect. Abstract: Previously, we reported that active vitamin D deficiency in mice causes secondary hypertension and cardiac dysfunction, but the underlying mechanism remains largely unknown. To clarify whether exogenous active vitamin D rescues hypertension by normalizing the altered central renin–angiotensin system (RAS) via an antioxidative stress mechanism, 1-alpha-hydroxylase [1α(OH)ase] knockout mice [1α(OH)ase –/– ] and their wild-type littermates were fed a normal diet alone or with 1, 25-dihydroxyvitamin D3 [1, 25(OH)2 D3 ], or a high-calcium, high-phosphorus "rescue" diet with or without antioxidant N -acetyl-l -cysteine (NAC) supplementation for 4 weeks. Compared with their wild-type littermates, 1α(OH)ase –/– mice had high mean arterial pressure, increased levels of renin, angiotensin II (Ang II), and Ang II type 1 receptor, and increased malondialdehyde levels, but decreased anti-peroxiredoxin I and IV proteins and the antioxidative genes glutathione reductase ( Gsr ) and glutathione peroxidase 4 ( Gpx4 ) in the brain samples. Except Ang II type 1 receptor, these pathophysiological changes were rescued by exogenous 1, 25(OH)2 D3 or NAC plus rescue diet, but not by rescue diet alone. We conclude that 1, 25(OH)2 D3 normalizes the altered central RAS in 1α(OH)ase –/– mice, at least partially, through a central antioxidative mechanism.